2000
DOI: 10.1063/1.1288910
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between dust grains in a dusty plasma

Abstract: Dust grains in plasma acquire a large negative charge, and can constitute a strongly coupled system. If the plasma is stationary, the plasma-mediated electrostatic potential around a single grain can be calculated by orbital-motion-limited (OML) theory, including ion absorption at the grain surface. This potential is repulsive at all ranges, and falls off as r−2 at long range. Nonlinear modifications occur when there are several grains, but the interaction is still repulsive. If the plasma is streaming by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
230
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(246 citation statements)
references
References 36 publications
15
230
1
Order By: Relevance
“…Numerically calculated equipotential contours near a charged dust grain in a plasma in which the ions are flowing past the grain from left to right along the z-axis of cylindrical coordinates. 17 The grain's surface potential is negative. The coordinates are in units of the characteristic Debye shielding length l D in the plasma.…”
Section: Noctilucent Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerically calculated equipotential contours near a charged dust grain in a plasma in which the ions are flowing past the grain from left to right along the z-axis of cylindrical coordinates. 17 The grain's surface potential is negative. The coordinates are in units of the characteristic Debye shielding length l D in the plasma.…”
Section: Noctilucent Cloudsmentioning
confidence: 99%
“…Figure 6 shows the result of a PIC calculation, by Martin Lampe and colleagues at the Naval Research Laboratory in Washington, DC, of the three-dimensional potential around a negatively charged dust grain immersed in a plasma with flowing ions. 17 Although the upstream potential is typical for a shielded negative grain, a complex structure downstream shows an electrostatic wakefield formed by positive ions that are focused into the region immediately behind the grain. The calculated formation of this positive region helps explain a pervasive experimental observation in dust crystals-namely, the tendency for grains to align directly behind one another along the direction of ion streaming.…”
Section: Noctilucent Cloudsmentioning
confidence: 99%
“…Horizontal confinement is often due to depressions in the plasma potential created by secondary electrodes. The interaction between dust particles is screened by the response of the electrons and ions so that the potential a distance r from a dust particle is given by a Yukawa (screened Coulomb or Debye-Hückel) potential [4,5] V (r) = 1 4π 0…”
mentioning
confidence: 99%
“…However, this approach is still far from a quantitative self-consistent description of the process. This becomes evident from a recent comprehensive analysis of the ion shielding of dust grains by Lampe et al, 16 where the effective shielding length was found 40% larger than the linearized Debye length. This shows that the question of the appropriate shielding length for a highly charged dust grain is far from settled.…”
Section: ϫ2mentioning
confidence: 89%